Structural basis of SspB-tail recognition by the zinc binding domain of ClpX - Park, Eun Young; Lee, Byung-Gil; Hong, Seung-Beom; Kim, Hyung-Wook; Jeon, Hyesung; Song, Hyun Kyu (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2007)
The degradation of ssrA(AANDEN-YALAA)-tagged proteins in the bacterial cytosol is carried out by the ClpXP protease and is markedly stimulated by the SspB adaptor protein. It has previously been reported that the amino-terminal zinc-binding domain of ClpX (ZBD) is involved in complex formation with the SspB-tail (XB: ClpX-binding motif). In an effort to better understand the recognition of SspB by ClpX and the mechanism of delivery of ssrA-tagged substrates to ClpXP, we have determined the structures of ZBD alone at 1.5, 2.0, and 2.5 angstrom resolution in each different crystal form and also in complex with XB peptide at 1.6 angstrom resolution. The XB peptide forms an antiparallel beta-sheet with two beta-strands of ZBD, and the structure shows a 1:1 stoichiometric complex between ZBD and XB, suggesting that there are two independent SspB-tail-binding sites in ZBD. The high-resolution ZBD: XB complex structure, in combination with biochemical analyses, can account for key determinants in the recognition of the SspB-tail by ClpX and sheds light on the mechanism of delivery of target proteins to the prokaryotic degradation machine. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: SPECIFICITY-ENHANCING FACTOR; N-TERMINAL DOMAIN; AAA PLUS PROTEASE; ESCHERICHIA-COLI; MOLECULAR CHAPERONE; CRYSTAL-STRUCTURE; SUBSTRATE; DEGRADATION; ADAPTER; PROTEOLYSIS